Functional Metagenomics Reveals Previously Unrecognized Diversity of Antibiotic Resistance Genes in Gulls - Martiny, Adam C. (Frontiers Research Foundation, 2011)
Wildlife may facilitate the spread of antibiotic resistance (AR) between human-dominated habitats and the surrounding environment. Here, we use functional metagenomics to survey the diversity and genomic context of AR genes in gulls. Using this approach, we found a variety of AR genes not previously detected in gulls and wildlife, including class A and C β-lactamases as well as six tetracycline resistance gene types. An analysis of the flanking sequences indicates that most of these genes are present in Enterobacteriaceae and various Gram-positive bacteria. In addition to finding known gene types, we detected 31 previously undescribed AR genes. These undescribed genes include one most similar to an uncharacterized gene in Verrucomicrobium and another to a putative DNA repair protein in Lactobacillus. Overall, the study more than doubled the number of clinically relevant AR gene types known to be carried by gulls or by wildlife in general. Together with the propensity of gulls to visit human-dominated habitats, this high diversity of AR gene types suggests that gulls could facilitate the spread of AR.